2016
DOI: 10.1007/s40291-016-0200-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Circulatory RNA-Based Biomarker Panel in Hepatocellular Carcinoma

Abstract: The circulatory RNA-based biomarker panel can serve as a potential biomarker for HCC diagnosis and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 49 publications
0
32
0
Order By: Relevance
“…1, 287 articles from databases were initially identified; titles and abstracts were reviewed after 98 duplicated articles were excluded; due to letters, reviews, meta-analyses, or irrelevant research topic, further 166 articles were excluded, leaving 23 articles for full-text review; as a result, 13 articles were finally excluded due to unrelated to cancer diagnosis, insufficient data, or irrelevant to our topic. Finally, 10 articles [2736] containing 19 studies were identified.…”
Section: Resultsmentioning
confidence: 99%
“…1, 287 articles from databases were initially identified; titles and abstracts were reviewed after 98 duplicated articles were excluded; due to letters, reviews, meta-analyses, or irrelevant research topic, further 166 articles were excluded, leaving 23 articles for full-text review; as a result, 13 articles were finally excluded due to unrelated to cancer diagnosis, insufficient data, or irrelevant to our topic. Finally, 10 articles [2736] containing 19 studies were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Long Non-Coding RNA MALAT1 Regulates ZEB1 Expression by Sponging miR-143-3p and Promotes Hepatocellular Carcinoma Progression [28]. The lncRNA-CTBP has also been identified had high sensitivity and specificity for discriminating HCC from healthy controls and also from CH patients [29]. Tang et al also published the results that lncRNAs might act as biomarker for the diagnosis of HCC from healthy control and CH patients [30].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of lncRNA and miRNAs has been also studied. lncRNA-CTBP, miR-16-2, miR-21-5p and LAMP2 had high sensitivities (91%, 92.3%, 93.6% and 92.3% respectively) for discriminating HCC from healthy subjects and also from chronic hepatitis C patients (75%, 88.9%, 88.9% and 94.9% respectively) [123] . miR-224 was highly expressed in HCC tissue and plasma, and after surgery the levels were normalized suggesting that miR-224 could reflect tumor dynamisms.…”
Section: Circulating Mirnasmentioning
confidence: 98%